PERSPEKTIF HUKUM EKONOMI ISLAM PADA PRAKTIK JUAL BELI KETELA POHON DENGAN SISTEM NGIJO DI DESA BUMIHARJO KECAMATAN GLENMORE KABUPATEN BANYUWANGI - Komarudin A; Habiburrahman Al Kholili (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The purpose of this study was to determine the buying and selling practice of cassava with the ngijo system in Bumiharjo Village, Glenmore District, Banyuwangi Regency. And to find out the perspective of Islamic economic law on the practice of buying and selling of cassava with the ngijo system, Bumiharjo Village, Glenmore District, Banyuwangi Regency. The results of this study are the practice of buying and selling cassava as follows: first, the seller will offer cassava, then the buyer will come to survey and make some estimates of the price of cassava, after being surveyed, bargaining will be made to reach an agreement with farmers, after that from the buyer The cassava pays an advance payment (panjer) as a sign and the rest is paid when the cassava is harvested. This cassava buying and selling transaction with the ngijo system in Bumiharjo Village is valid according to the perspective of Islamic law, because it is in accordance with the pillars and terms of sale and purchase, namely: aqidain, ma'qud alaih, and shighat and avoid several possible facades, such as usury and gharar.